Quality of life assessment in schwannomatosis – A systematic review - Anna C. Lawson McLean; Steffen K. Rosahl; Aaron Lawson McLean; Pascal Fehringer; Anna Freier; Denise Löschner; Marcel A. Kamp; Christian Senft; Andreas K. Demetriades (Brain and Spine)
Introduction: The term schwannomatosis refers to rare genetic disorders characterized by the development of multiple tumors within the central and/or peripheral nervous system. Recent advancements in our molecular understanding of these disorders have led to a redefined conceptual framework within the field, grouping NF2-related schwannomatosis with other forms of schwannomatosis. Research question: This systematic review aims to compile and analyse existing literature on QoL in individuals with schwannomatosis. Methods: A comprehensive search of electronic databases was conducted up until January 2025. Inclusion criteria included studies evaluating QoL in adults with schwannomatosis, using validated QoL assessment tools or patient-reported outcome measures. There were no geographical or time restrictions placed on the search. Case reports and reviews were excluded from the analysis to focus on original research contributions. Results: The initial search identified 241 articles, after removal of duplicates. Three articles were added after screening references. 40 articles were selected for final analysis. These studies utilized various assessment tools, including PHQ-9 (n = 10), WHOQOL-BREF (n = 9) and the disease-specific questionnaire NFTI-QOL (n = 15). The collective findings consistently indicated compromised QoL among individuals with schwannomatosis, particularly in domains such as physical functionality, pain perception, emotional well-being, and social interactions. Discussion and conclusion: This systematic review reveals substantial variability in QoL assessment for schwannomatosis, highlighting significant physical and psychological impacts in NF2-SWN and predominant bodily pain in non-NF2-SWN patients. We call for an international, interdisciplinary consensus on standardized QoL tools to enable clearer research comparisons, guide clinical practice, and improve patient-centered care.